2021
DOI: 10.1371/journal.ppat.1009733
|View full text |Cite
|
Sign up to set email alerts
|

pMGF505-7R determines pathogenicity of African swine fever virus infection by inhibiting IL-1β and type I IFN production

Abstract: Inflammatory factors and type I interferons (IFNs) are key components of host antiviral innate immune responses, which can be released from the pathogen-infected macrophages. African swine fever virus (ASFV) has developed various strategies to evade host antiviral innate immune responses, including alteration of inflammatory responses and IFNs production. However, the molecular mechanism underlying inhibition of inflammatory responses and IFNs production by ASFV-encoded proteins has not been fully understood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
110
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 55 publications
2
110
0
Order By: Relevance
“…Specifically, in terms of IFN response, A528R promotes the expression of the autophagyrelated protein ULK1 to degrade STING and suppress IFN induction [15]. A528R also interacts with IRF3 to inhibit its nuclear translocation and block type I IFN production [14]. In terms of inflammation, A528R interacts with IKKα to inhibit IL-1β gene transcription and with NLRP3 to block proIL-1β maturation and secretion [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, in terms of IFN response, A528R promotes the expression of the autophagyrelated protein ULK1 to degrade STING and suppress IFN induction [15]. A528R also interacts with IRF3 to inhibit its nuclear translocation and block type I IFN production [14]. In terms of inflammation, A528R interacts with IKKα to inhibit IL-1β gene transcription and with NLRP3 to block proIL-1β maturation and secretion [14].…”
Section: Discussionmentioning
confidence: 99%
“…A528R also interacts with IRF3 to inhibit its nuclear translocation and block type I IFN production [14]. In terms of inflammation, A528R interacts with IKKα to inhibit IL-1β gene transcription and with NLRP3 to block proIL-1β maturation and secretion [14]. In our study, we found A528R interacts with NF-κB p65 to inhibit NF-κB activation, but we did not exclude other signaling proteins upstream p65, such as IKKα/β/γ complex, which may be modulated by A528R.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASFV has been reported to inhibit signaling in the cGAS-STING pathway and downregulate IFN-β levels when porcine macrophages are infected with the ASFV Armenia/07 virulent strain ( García-Belmonte et al., 2019 ). MGF-505-7R and MGF-505-11R interact with STING, inhibit the cGAS-STING signaling pathway and subvert type I IFN production ( Li et al., 2021a ; Yang K. et al., 2021 ). DP96R of the ASFV China 2018/1 strain is reported to negatively regulate type I IFN expression and NF-κB signaling by inhibiting both TBK1 and IKKβ ( Wang et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, DP96R of ASFV China 2018/1 was reported to negatively regulate IFN-I expression and NF-kB signaling by inhibiting both TBK1 and IKKb (Wang et al, 2018). MGF-505-7R interacts with IKKa, STING, and IRF3 and inhibits the cGAS-STING signaling pathway to block IFN-b and inhibit pro-inflammatory IFN-gmediated JAK-STAT1 signaling (Li J. et al, 2021;Li et al, 2021a;Li et al, 2021b). E120R interacts with IRF3 and interferes with recruitment of IRF3 to TBK1, which in turn suppresses IRF3 phosphorylation, decreasing IFN production (Liu H. et al, 2021).…”
mentioning
confidence: 99%